THE IMPACT OF ILLUSION OF CONTROL, OVERCONVIDENCE AND EMOTIONS ON INVESTMENT DECISIONS MADE BY YOUNG INVESTORS IN THE CITY OF MAKASSAR - Syariati, Alim; Sumarlin, Sumarlin; Ainun, A. Nur Asri (Jurnal Iqtisaduna, 2020)
Young investors are unique in terms of making investment decisions. This study aims to examine the impact of illusion of control, overconvidence and emotion on investment decisions made by young investors in the city of Makassar. Using quantitative method, 114 investors are available as participants to answer the questionnaire of this research. The sampling technique used is accidental sampling. The results of the study show that Illusion of Control partially has a positive and significant impact on investment decisions. Overconvidence partially has a positive and significant impact on investment decisions. Emotions partially have a positive and significant impact also on investment decisions. Simultaneously illusion of control, overconvidence and emotion have a positive and significant effect on investment decisions. The findings of this study show that young investors in the city of Makassar involve psychological bias in making investment decisions.